The Effect Of Moles (Local Microorganisms) Of Banana Peel And Fruit Peel On The Growth Of Stems, Leaves, and Roots Of Tomato Plants - Choirunisa, Khusnul; Aringsih, Putri Silviana; Nur Fauziah, Daniar Eka; Siwi, Herwening Widya; Khofidhoh, Siti Nur; Setyaningsih, Endang (Advances In Social Humanities Research, 2024)
Local microorganisms (MOL) are one of the means in helping the process of plant growth made from organic materials. In this study, MOL was made from banana peels and other fruit skins, and java sugar was added when fermented for two weeks. Its use is carried out with four treatments: control, 1: 2, 2: 1, and 3 days. This study used quantitative data by observing the growth of tomato plants (Solanum lycopersicum) for 21 days, which experienced significant changes in their growth. Banana peel contains macro elements C, N, P, and K. Meanwhile, Javanese sugar in MOL can be used by microorganisms to obtain glucose for food. Local microorganisms have environmentally friendly properties and can help the plant growth process by working in the soil through plant roots. Despite these findings, the study exhibits limitations in experimental control and measurement of other variables influencing tomato plant growth beyond MOL utilization. Additionally, the significance of observed growth changes lacks clarity, warranting further investigation.